ANALISIS PERAN KAUM MUDA DALAM GEREJA BERDASARKAN DOKUMEN CHRISTUS VIVIT PAUS FRANSISKUS - Refo, Ignasius (Fides et Ratio : Jurnal Teologi Kontekstual Seminari Tinggi St. Fransiskus Xaverius Ambon, 2024)
The role of youth within the Church is pivotal yet currently challenged by various factors impacting their active participation in religious activities. Significant decline in youth attendance at mass and low engagement in church and Catholic organizations are becoming pressing issues for the Church, which seeks to remain relevant to younger generations. This study, guided by the document Christus Vivit by Pope Francis, aims to analyze the challenges faced by youth and the opportunities for their empowerment within the Church. A qualitative approach, particularly library research, was employed to conduct an in-depth analysis of Christus Vivit alongside other relevant Church documents and academic literature. Data were organized into key themes including the role of youth, challenges of secularization, identity crisis, and the influence of social media. The findings reveal that secularization and social media significantly shape the youth's perception of religion, often leading to a sense of detachment from Church values. However, Christus Vivit highlights that youth are not just the future but the present of the Church, capable of bringing innovation and vitality if adequately supported. Effective pastoral care, inclusive mentorship, and leveraging technology for evangelization are essential strategies for empowering youth. The study concludes that the Church must adopt a responsive and inclusive approach to engage youth, addressing their unique challenges while fostering their active involvement in Church life. This requires collaborative efforts between Church leaders, parents, and educators to create an environment that supports the spiritual and personal growth of the youth, ensuring their integral role in the Church today and in the future.